A-Priority and Hermeneutics: The Scientificity of Phenomenology from Husserl to Heidegger - Cassara, Bruno (Bollettino Filosofico, 2020)
Like Husserl, the young Heidegger was preoccupied with the a-priority of phenomenology. He also incorporates hermeneutics into phenomenology, though Husserl was convinced that the a-priority of phenomenology removed all interpretation from its analyses. This paper investigates how the early Heidegger is able to make hermeneutics a general condition of understanding while maintaining, in line with Husserl, that phenomenology is an a-priori science. This paper also provides insight into key debates in the history of phenomenology. I examine two places in which Heidegger departs from Husserl’s phenomenology – the doctrine of categorial intuition and the “as-structure” of understanding – to show that a-priority and hermeneutic understanding come together, ontically, in facticity as the only possible starting point for phenomenology. Ontologically, however, a-priority and hermeneutics come together in the co-affection of Dasein as understanding and being as pre-given. This co-affection is itself dependent on Temporality as “the condition of any possible earlier”. Keywords: Apriori, Heidegger, Hermeneutics, Husserl, Idea of Science